2009
DOI: 10.1002/aehe.3406
|View full text |Cite
|
Sign up to set email alerts
|

Table of Contents

Abstract: Executive SummaryForewordAcknowledgmentsThe Development of Doctoral Students: Phases of Challenge and SupportWhy Do We Need to Understand Doctoral Students' Development?Why Have Doctoral Students Been Forgotten?How Do Doctoral Students Develop?A Model of Doctoral Student DevelopmentOrganization of the MonographStudent Development Theory: A PrimerDefining Student DevelopmentPsychosocial DevelopmentSocial Identity DevelopmentRacial Identity DevelopmentCognitive DevelopmentConclusionUnderstanding Doctoral Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 87 publications
(140 reference statements)
0
31
0
1
Order By: Relevance
“…This synthesis of the scholarship on doctoral education is framed within an alignment of the heroic journey monomyth described by Campbell (2008) to the progression of doctoral student experiences (Gardner, 2009). Various movie characters are used to illustrate the three primary stages of the heroic journey: the departure, initiation, and the return.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This synthesis of the scholarship on doctoral education is framed within an alignment of the heroic journey monomyth described by Campbell (2008) to the progression of doctoral student experiences (Gardner, 2009). Various movie characters are used to illustrate the three primary stages of the heroic journey: the departure, initiation, and the return.…”
Section: Methodsmentioning
confidence: 99%
“…The research on doctoral student success and attrition has identified several potential sources for this disconnect (e.g., Ehrenberg, Jakubson, Groen, So, & Price, 2007;Golde, 1998;Rockinson-Szapkiw, Spaulding, & Spaulding, 2016). Rather than instrumental needs such as finances and the environmental challenges of family and work however, the focus of this conceptual paper is on the internal struggles of becoming a person who holds a doctorate (Gardner, 2009;Yazdani & Shokooh, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cierto es que estos trayectos curriculares no garantizan una correlación directa con el desarrollo de habilidades de investigación a corto plazo; como señala Moreno Bayardo (2005:524), "existe una notable diferencia entre aprobar cursos de metodología y saber investigar". No obstante, en dependencia del enfoque de los cursos y en sinergia con otros factores, puede favorecer el camino hacia la independencia al que refiere Gardner (2009).…”
Section: Formación En Metodología De La Investigación Educativaunclassified
“…According to Blass, Jasman and Levy (2012), the TPI practice is a personal issue; tutors must have as their main concern to find ways to help and guide their students throughout the research project development process (Gardner, 2009); this acquires great importance when it comes to the orientation and skills that a student needs to acquire during the work carried out with the tutor (Hernández & Díaz, 2010) and the implementation of the research project.…”
Section: Reference Frameworkmentioning
confidence: 99%